2021
DOI: 10.1097/cce.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Pao 2: A Continuous and Noninvasive Method to Estimate Pao 2 and Oxygenation Index

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
(62 reference statements)
2
6
0
Order By: Relevance
“…We showed that machine learning models outperformed previously published equations in terms of imputing PaO 2 from SpO 2 in the mechanically-ventilated adult population. Consistent with our findings, Sauthier et al, utilized neural network models to validate a continuous and noninvasive method of hypoxemia estimation in pediatric population 28 . They utilized convolutional neural network (CNN), long short-term memory network (LSTM), and multilayer perceptron (MLP) to impute PaO 2 .…”
Section: Discussionsupporting
confidence: 88%
“…We showed that machine learning models outperformed previously published equations in terms of imputing PaO 2 from SpO 2 in the mechanically-ventilated adult population. Consistent with our findings, Sauthier et al, utilized neural network models to validate a continuous and noninvasive method of hypoxemia estimation in pediatric population 28 . They utilized convolutional neural network (CNN), long short-term memory network (LSTM), and multilayer perceptron (MLP) to impute PaO 2 .…”
Section: Discussionsupporting
confidence: 88%
“…This frequency of Spo 2 measurements greater than 97% is consistent with data from many other ICU cohorts (20)(21)(22)(23). We thus used the estimated Pao 2 /Fio 2 ratio (ePF ratio), as described by Sauthier et al (24) to overcome this problem. For every available data point, ePao 2 was estimated from the Spo 2 using equation by Sauthier et al (24) valid across all values of Spo 2 .…”
Section: Research In Contextsupporting
confidence: 73%
“…This frequency of Sp o 2 measurements greater than 97% is consistent with data from many other ICU cohorts (20–23). We thus used the estimated Pa o 2 /F io 2 ratio (ePF ratio), as described by Sauthier et al (24) to overcome this problem. For every available data point, ePa o 2 was estimated from the Sp o 2 using equation by Sauthier et al (24) valid across all values of Sp o 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Ventilator data were obtained through a continuous data feed to the monitor, and when this data feed was not set up or disconnected, some variables were not available. When a capillary blood gas was used, PaO 2 was estimated from SpO 2 , using the reported formula by Sauthier et al to calculate OI and PF ratio [18]. with the closest blood gas to the time point of interest, which was within the time window, identified for the analysis.…”
Section: Variable Definitionmentioning
confidence: 99%